Variation and genetic structure of the endangered Lepus flavigularis (Lagomorpha: Leporidae) - Cruz Salazar, Bárbara; Lorenzo, Consuelo; Espinoza Medinilla, Eduardo; López, Sergio (Revista de Biología Tropical, 2017)
Lepus flavigularis, is an endemic and endangered species, with only four populations inhabiting Oaxaca, México: Montecillo Santa Cruz, Aguachil, San Francisco del Mar Viejo and Santa María del Mar. Nevertheless, human activities like poaching and land use changes, and the low genetic diversity detected with mitochondrial DNA and allozymes in previous studies, have supported the urgent need of management strategies for this species, and suggest the definition of management units. For this, it is necessary to study the genetic structure with nuclear genes, due to their inheritance and high polymorphism, therefore, the objective of this study was to examine the variation and genetic structure of L. flavigularis using nuclear microsatellites. We sampled four populations of L. flavigularis and a total of 67 jackrabbits were captured by night sampling during the period of 2001 to 2006. We obtained the genomic DNA by the phenol-chloroform-isoamyl alcohol method. To obtain the diversity and genetic structure, seven microsatellites were amplified using the Polymerase Chain Reaction (PCR); the amplifications were visualized through electrophoresis with 10 % polyacrylamide gels, dyed with ethidium bromide. Genetic diversity was determined using the software GenAlEx v. 6.4, and genetic structure was obtained with ARLEQUIN v. 3.1; null alleles were evaluated using the program Micro-Checker v.2.2.2. Additionally, a Bayesian analysis was performed with software STRUCTURE v. 2.2.3., and the isolation by distance (IBD) was studied using the program PASSAGE v.2.0.11.6. Our results showed that the genetic variation found was low (HO = 0.30, HE = 0.24) when compared to other jackrabbit species. Fixed alleles and moderate levels of genetic differentiation (FST = 0.18, P = 0.001) were detected among populations, indicating the effect of the genetic drift and limited gene flow. Bayesian clustering analysis revealed two groups: (1) jackrabbits from Montecillo Santa Cruz, and (2) individuals living in Aguachil, San Francisco del Mar Viejo and Santa María del Mar. No evidence was found of isolation by distance. It is possible that the geographic barriers present between populations (e.g. lagoons, human settlements), rather than the geographical distance between them, may explain the observed genetic structure. The inbreeding coefficient was negative (FIS = -0.27, P = 0.03), indicating genetic sub-structure in populations. We suggest two management units based on the genetically closer populations, which will help define precise conservation actions in L. flavigularis. This research is the basis for defining translocation of individuals between populations, nevertheless, a more extensive future study, with specific molecular markers for L. flavigularis, is required. In addition, it is necessary to analyze the barriers that limit the gene flow, since it is urgent to reduce the genetic differentiation between populations and increase the genetic diversity of this species.